Biological and molecular characterization of Panstrongylus sp. native of Peru - Jeri Apaza, Cesar Hugo (2020)
Objective. To determine the biological and molecular characteristics of the Panstrongylus sp. native to northern Peru. Methods. Observational, descriptive study. Biological material from 5 different regions of northern Peru was used, and a sample of 50 specimens was selected by intentional sampling. For the characterization of the specimens at the molecular level, the ITS-2 marker of ribosomal DNA was used, using the PCR technique. Results. 100% of the samples were classified as Panstrongylus herreri. At the molecular level, 3 different patterns of the ITS-2 band were observed: 960bp, 800bp and 750bp. Conclusion. 100% of the samples were Panstrongylus herreri, captured in intra-household environments in northern regions of Peru, with an ITS-2 pattern.